Kajian Kritis Peraturan Penanggulangan Ujaran Kebencian dalam Pasal 2 Ayat 45a Undang-Undang Nomor 1 Tahun 2024 dari Perspektif Maqasid Al-Syariah - Muhammad; Azzer Arifuddin; Farahdilla Mutiara Khansa; Andi Muh. Taqiyuddin BN; Samsidar Jamaluddin (STIH Zainul Hasan Kraksaan Kraksaan, 2025)
This study aims to explain the regulation of hate speech mitigation in Article 45A(2) of Law No. 1 of 2024 and to examine the criticism of Maqasid Al Syari'ah against the regulation of hate speech mitigation in Article 45A(2) of Law No. 1 of 2024. This study is a qualitative research. The research design is a literature review. The findings of this study indicate that: First, Article 45A(2) of Law No. 1 of 2024 is a legislative effort to address the spread of hate speech based on ethnicity, religion, and race through electronic media. By understanding and complying with these provisions, the public is expected to contribute to creating an inclusive and harmonious digital space. However, the success of implementing this regulation depends heavily on consistent law enforcement, strengthening digital literacy, and collaboration between the government, the public, and social media platforms. With a holistic approach, it is hoped that this regulation can become an effective instrument in creating a safe and inclusive digital space. Second, Maqasid al Syari'ah's criticism of the hate speech mitigation regulation in Article 2 of Section 45A of Law No. 1 of 2024, namely that the regulation is not yet fully considered in line with the preservation of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-'aql), lineage (hifz al-nasl), and property (hifz al-mal).